Palatalization of Javanese Consonant Allophones Osing Dialect in Kendhang Kempulan Songs on The Album Lagu-Lagu Banyuwangi Ngetop Sumiyati - Irakusuma, Ratna Nur Fatimah; Winarti, Daru; Salahuddin, Salahuddin (International Journal of Multidisciplinary Sciences, 2025)
The people of Osing, Banyuwangi, have unique consonant allophones in their speech. Still a dialect of Javanese, the realization of the phoneme of the Osing dialect shows significant differences with the standard variety of Javanese. In the Osing dialect, there are a number of consonant phonemes which in reality are pronounced with a y sound with the meaning of the word that does not change even if the y sound is omitted. Against the background of these problems, this study aims to identify the palatalization of the consonant allophone of the Javanese Osing dialect. Data was collected from kendhang kempulan songs in the album "Lagu-Lagu Banyuwangi Ngetop Sumiyati", then words whose consonant sounds underwent palatalization were collected. Clacification of the realization of palatalized consonant sounds above, then produces ten (10) consonant sounds whose allophones undergo palatalization, those are [by], [my], [dy], [ḍy], [ny], [gy], [wy], [ry], [ly], and [jy]. There is also a vowel sound pattern that follows the palatalized consonant sounds above, given that palatalization of consonant allophones is not followed by all vowel phonemes or allophones.